Synthesis and study of cholosubstituted 4-aroyl pyrazolines and isoxazolines and their effects on inorganic ions in blood serum in albino rats - AMOL D. BHOYAR; GANESH N. VANKHADE; PRITHVISIGH R. RAJPUT (Nusantara Bioscience, 2011)
Abstract. Bhoyar AD, Vankhade GN, Rajput PR. 2011. Synthesis and study of cholosubstituted 4-aroyl pyrazolines and isoxazolines and their effects on inorganic ions in blood serum in albino rats. Nusantara Bioscience 3: 118-123. Condensation of 2-substituted 3,5-dichloroacetophenone (2a-b) obtained from the condensation of 2-hydroxy 3,5-dichloro-acetophenone (1) and benzoyl chloride were dissolved in NaOH, on treatment under Baker-Venkatraman transformation in presence of KOH with pyridine gives 1-(2-hydroxy-3,5-dichlorophenyl)-3-substituted-1,3-propanediones (3a-b). Then converted into 3-aroyl-6,8-dichloroflavanones (4a-d) by using different aromatic aldehyde in ethanol containing little piperidine. The condensation of (4a-d) and phenylhydrazine hydrochloride, piperidine in DMF gives 3-(2-hydroxy3,5-dichlorophenyl)-4-substitution-1-phenyl-D2pyrazolines (5a-d) and condensation of (4a-d) and hydroxylamine-hydrochloride gives 3-(2-hydroxy-3,5-dichlorophenyl)-4-aroyl-5-substituted isoxazolines (6a-d). The above compounds are screened for their activities and have been found to exhibit significant effects on inorganic ions in blood serum in albino rats.